Summer Surgical Elective in Hong Kong - Ho, Martin; Chow, Velda (International Journal of Medical Students, 2024)
I completed a surgical elective with the Department of Plastic and Reconstructive Surgery in Queen Mary Hospital, Hong Kong Special Administrative Region (SAR), China. I was taught a great deal of surgical knowledge by the team and was inspired as I witnessed the life-changing operations they performed. The experience was professionally and culturally enriching and has cemented my desire to pursue surgery as a career to improve the lives of my future patients. In this article, I will discuss how I secured this elective and my personal experience during the elective. Additionally, I will briefly discuss some differences I observed between the healthcare systems in Hong Kong and Ireland, including different scopes of surgical practice, residency training, and also the similar challenges faced by both public healthcare systems.